2005
DOI: 10.1021/jf049267y
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption between β-Casein or β-Lactoglobulin and Model Milk Membrane Lipids at Oil−Water Interfaces

Abstract: This study investigated the competitive adsorption between milk proteins and model milk membrane lipids at the oil-water interface and its dependence on the state of the lipid dispersion and the formation of emulsions. Both protein and membrane lipid surface load were determined using a serum depletion technique. The membrane lipid mixture used was a model milk membrane lipid system, containing dioleoylphosphatidylcholine, dioleoylphosphatidylethanolamine, milk sphingomyelin, dioleoylphosphatidylserine, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…As discussed below, it is likely that that some streptavidin is bound to biotinylated lipid on the LC interface (via biotin-streptavidin binding) or co-exists along with phospholipid in an adsorbed state on the LC interface. 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed below, it is likely that that some streptavidin is bound to biotinylated lipid on the LC interface (via biotin-streptavidin binding) or co-exists along with phospholipid in an adsorbed state on the LC interface. 45 …”
Section: Resultsmentioning
confidence: 99%
“…We conclude that it is likely that the phospholipid exists at the LC interface in at least two states. 45 One state of the phospholipid interacts with the LC, and thus contributes to the observed ordering of the LC. A second population of phospholipid, while bound to the interfacial region, likely does not interact directly with the LCs but is bound to the streptavidin at the LC interface (e.g., adsorbed vesicles).…”
Section: Resultsmentioning
confidence: 99%
“…6A, C and E). As the phospholipidrich beta-serum was added to the protein aqueous phase before injection of the oil phase and emulsification, it is anticipated that phospholipids and proteins are both competing and interacting at the interface of the Concept IMF fat droplets, and thus form a mixed protein-phospholipid monolayer [45]. Fig.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Waninge et al (Waninge et al, 2005) studied the interaction between β-lactoglobulin and β-casein and milk membrane lipids at the oil-aqueous interface in emulsions. They found that the membrane lipid emulsified emulsions were dominated by the membrane lipids even after equilibrium with protein solutions.…”
Section: Role Of Protein-emulsifier Interactions In Real Food (And Phmentioning
confidence: 99%